Pengaruh Tabungan Mudharabah Dan Pembiayaan Musyarakah Terhadap Laba: Studi Kasus Pada Lima Bank Syariah Nasional - Febiola, Zhalzha; Suardy, Weman; Rosa, Edy Safni (Jurnal Ilmiah Manajemen Kesatuan, 2021)
This study aims to determine (1) Does mudharabah savings have a significant effect on bank profits? (2) Does musyarakah financing have a significant effect on bank profit? (3) Do mudharabah savings and musyarakah financing together have a significant effect on bank profits? The analytical method used in this research is multiple linear regression with the total profit being the dependent variable and two independent variables, namely Mudharabah Savings and Musharaka Financing. The results of data processing have obtained a regression model Y = 36964 + 0.021X1 + -0.002X2. The regression coefficient shows that if each mudharabah savings is 0.021 one unit, it is predicted that it will increase the amount of savings by 36964 units and vice versa. The value of the coefficient of determination (R2) is 0.564, this indicates that the mudharabah savings and musharaka financing variables contribute or influence 56% on the variable amount of profit. Partially, the t test results indicate that each variable the amount of mudharabah savings has a significant effect on the amount of profit so that the hypothesis is accepted and the musyarakah financing has a significant negative effect on the amount of profit. Simultaneously, the results of the F test show that together mudharabah savings and musyarakah financing have a significant effect on total profit so that the hypothesis is accepted. Keywords: Mudharabah Savings, Musharaka Financing, Profit.